Penguatan Profesionalisme Guru Pendidikan Agama Islam berbasis Nilai-nilai Profetik - Faizin, Moh.; Bachtiyar, Machfud (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2021)
Through Law Number 14 of 2005 concerning teachers and lecturers, the teaching profession has an equal place with other professions. However, there is actually a fundamental thing that is sometimes not realized, namely the prophetic value of the teaching profession. Therefore, this study seeks to describe and analyze the implementation of strengthening the professionalism of Islamic Religious Education (PAI) teachers based on prophetic values ​​for PAI students at the Islamic Education Study Program, UIN Sunan Ampel Surabaya, along with the problems and impacts. This article is a qualitative research with rationalist and phenomenological approaches. This study found that, by implementing strengthening professionalism through prophetic values, learning objectives were easier to achieve and the quality of education was maintained. In the implementation process, several problems emerged that became obstacles, including: the scientific background of the lecturers, students' understanding of learning design, and supporting facilities. However, there are positive impacts from the implementation of the program, including: creating a pleasant learning atmosphere, developing cultural aspects of students, shaping the character of ideal teacher candidates, actualizing multicultural education, and trained students in implementing integrative learning. To be more optimal, it is important to always instill humanist values, such as tolerance, respect for the rights of others, and respect for diversity. More than that, the formation of the personality of a prospective teacher must be an agenda that is really prepared by the institution such as personality development.